Tumor-derived extracellular vesicle nucleic acids as promising diagnostic biomarkers for prostate cancer - Diao, Yanjun; Zhu, Bingbing; Ding, Ting; Li, Rui; Li, Jinjie; Yang, Liu; Zhou, Lei; Hao, Xiaoke; Liu, Jiayun (Frontiers in Oncology, 2023)
Liquid biopsy as a non-invasive method has a bright future in cancer diagnosis. Tumor-related extracellular vesicles (EVs) and their components (nucleic acids, proteins, and lipids) in biofluids may exert multiple functions in tumor growth, metastasis, immune escape, and angiogenesis. Among all the components, nucleic acids have attracted the most interest due to their simplicity of extraction and detection. In this review, the biological functions of EVs in prostate cancer (PCa) genesis and progression were summarized. Moreover, the diagnostic value of EV RNA markers found in clinical body fluid samples was reviewed, including their trends, challenging isolation methods, and diagnostic efficacy. Lastly, because relatively much progress has been made in PCa, studies on EV DNA markers are also discussed.